The Relationship Between Body Mass Index (BMI) and Age at Menarche Among Adolescent Girls - Devi Hartati; Citra Dewi Anitasari; Khilda Durrotun Nafisah (Jurnal Ilmu Kesehatan Abdurrab, 2025)
Background: The normal age of menarche typically occurs between 10 and 16 years, with an average age of 12–13 years. Early menarche increases the risk of developing polycystic ovary syndrome (PCOS), emotional disturbances, depression, and risky sexual behaviour. Conversely, delayed menarche may indicate chronic malnutrition, endocrine disorders, or psychosomatic stress, all of which can affect fertility in adulthood. Objective: This study aimed to determine the relationship between Body Mass Index (BMI) and the age of menarche among adolescent girls. Methods: This research employed a quantitative design with a cross-sectional approach. The study population consisted of female students at SMKN 2 Siak Hulu. A total of 56 respondents were selected using total sampling. Data were analysed using univariate and bivariate analyses. Prior to bivariate testing, the Chi-Square (χ²) test was conducted to determine associations between variables. Results: The findings revealed that among the 56 respondents, 71.4% had a normal BMI, 56.9% did not experience stress, and 75% had a normal menstrual cycle. There was no significant relationship between BMI and menstrual cycle disorders among the students at SMKN 2 Siak Hulu (p = 0.840). Similarly, no significant relationship was found between stress and menstrual cycle disorders (p = 0.343). Keywords: BMI, Age at Menarche, Adolescent Girls